Sodium Tripolyphosphate and Polyphosphate as Dispersing Agents for Alumina Suspensions: Rheological Characterization. (4th June 2013) - Piani, L.; Papo, A.
Abstract : In the present work, the influence of addition of some dispersing agents employed for maximizing the solid loading of alumina concentrated suspensions has been investigated. Two commercially available deflocculants were used: a sodium tripolyphosphate and a sodium polyphosphate. Rheological tests were carried out at 25°C under continuous flow conditions by using the rate-controlled coaxial cylinder viscometer Rotovisko-Haake 20, system M5-osc., measuring device SV2P with serrated surfaces. The application of rheological techniques permitted the evaluation of the efficiency and the optimum dosage of the dispersing agents employed upon the alumina slips examined, that is, the critical concentration at which the maximum reduction in viscosity is detected.